Blood Ammonia Level Correlates with Severity of Cirrhotic Portal Hypertensive Gastropathy - Ferial El-Kalla; Loai Mansour; Abdelrahman Kobtan; Asmaa Elzeftawy; Lobna Abo Ali; Sherief Abd-Elsalam; Sahar Elyamani; Mohamed Yousef; I. Amer; H. Mourad; Mohamed Elhendawy (Gastroenterology Research and Practice)
Background. Portal hypertensive gastropathy (PHG) is a common anomaly with potential for bleeding found in portal hypertension. Blood ammonia levels correlate well with liver disease severity and existence of portosystemic shunts. Increased ammonia results in vasodilation and hepatic stellate cell activation causing and exacerbating portal hypertension. Objective. To assess the relation of blood ammonia to the presence and severity of portal hypertensive gastropathy in cirrhosis. Methods. This cross-sectional study included 381 cirrhotics undergoing screening for esophageal varices (EV) divided into a portal hypertensive gastropathy group (203 patients with EV and PHG), esophageal varix group (41 patients with EV but no PHG), and control group (137 patients with no EV or PHG). A full clinical examination, routine laboratory tests, abdominal ultrasonography, child score calculation, and blood ammonia measurement were performed for all patients. Results. Blood ammonia, portal vein, splenic vein, and splenic longitudinal diameters were significantly higher and platelet counts lower in patients with EV and EV with PHG than controls. Patients having EV with PHG had significantly higher bilirubin and ammonia than those with EV but no PHG. Severe PHG was associated with significantly higher ammonia, EV grades, and superior location and a lower splenic longitudinal diameter than mild PHG. The PHG score showed a positive correlation with blood ammonia and a negative correlation with splenic longitudinal diameter. Conclusions. Blood ammonia levels correlate with the presence, severity, and score of portal hypertensive gastropathy in cirrhosis suggesting a causal relationship and encouraging trials of ammonia-lowering treatments for the management of severe PHG with a tendency to bleed.